Modelling Torsade de Pointes arrhythmias in vitro in 3D human iPS cell-engineered heart tissue. Issue 1 (December 2017) - Kawatou, Masahide; Masumoto, Hidetoshi; Fukushima, Hiroyuki; Morinaga, Gaku; Sakata, Ryuzo; Ashihara, Takashi; Yamashita, Jun
Abstract Torsade de Pointes (TdP) is a lethal arrhythmia that is often drug-induced, thus there is an urgent need for development of models to test or predict the drug sensitivity of human cardiac tissue. Here, we present an in vitro TdP model using 3D cardiac tissue sheets (CTSs) that contain a mixture of human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes and non-myocytes. We simultaneously monitor the extracellular field potential (EFP) and the contractile movement of the CTSs. Upon treatment with IKr channel blockers, CTSs exhibit tachyarrhythmias with characteristics of TdP, including both a typical polymorphic EFP and meandering spiral wave re-entry. The TdP-like waveform is predominantly observed in CTSs with the cell mixture, indicating that cellular heterogeneity and the multi-layered 3D structure are both essential factors for reproducing TdP-like arrhythmias in vitro. This 3D model could provide the mechanistic detail underlying TdP generation and means for drug discovery and safety tests. Torsade de Pointes (TdP) is a life-threatening ventricular arrhythmia often caused by drugs. In response to an urgent need for human tissue TdP models, here the authors describe a 3D human iPS cell-engineered heart tissue that generates TdP in response to drugs, providing a suitable model for studies of TdP mechanism and drug toxicity.